Angular distribution of evaporated protons from 50-MeV-range proton-nucleus reactions - Yamaguchi Yuji; Uozumi Yusuke; Nakano Masahiro (EPJ Web of Conferences, 2016)
The angular distribution of compound reactions at bombarding energies lower than 10 MeV is known to be 90˚ symmetry. At the higher incident energies, 50-MeV range, the quantization axis tilts from the beam axis due to the particle emission in the cascade or the pre-equilibrium process. Therefore, it is necessary to know the tilted quantization axis for the angular distribution calculation of the evaporated protons from (p, p’x) reactions. In the present work, we applied the intranuclear cascade (INC) model to determine the tilted quantization axis by a classical vector analysis. The proton evaporation was calculated by the generalized evaporation model (GEM). By fitting calculations to experimental angular distributions, we deduced the angular momentum transfer from the equilibrium state.